Progressive muscular dystrophy in childhood - Dubowitz, Victor (Department of Paediatrics and Child Health, 2020)
The words of Gowers are as true today as they were nearly a century ago. My interest in muscular dystrophy started in 1957 when, as Senior House Officer at Queen Mary's Hospital for Children, Carshalton, Surrey, I first observed a large number of children suffering from this tragic disease. The frustration of helplessly, watching its inevitable course stimulated the present study.After obtaining an initial impression or' the collection from my clinical observations and a review of the hospital records between 1920 and 1950, I started a more systematic enquiry. The present investigation compromises my personal observations on 65 cases ranging in age from 3 to 16 years. Of these, 57 were seen and followed up at Queen Mary's Hospital for Children, and 8 at the Southern Hospital, Dartford, Kent.